Engagement and dialogic space in motherhood and mental illness: a qualitative study on personal blog posts on postnatal depression - Rautiainen, Pauliina (fi=Turun yliopisto|en=University of Turku|, 2017)
This thesis studies how women who have suffered or are currently suffering from postnatal depression discuss mental illnesses, motherhood, mothering and postnatal depression. The material in this study was collected from two different British websites called Time to Change and The Cedar House Support Group, and the data consisted of blog posts written by women who have suffered or are currently suffering from postnatal depression. The topic of the blog posts was the women’s personal experiences with postnatal depression. The analysis was done by using Martin and White’s Appraisal theory and more specifically Engagement. The study examined how the women engaged with different voices in the heteroglossic backdrop through evaluative language use. The study found that the women used contractive engagement strategies (proclaim and disclaim) distinctively more than expansive engagement strategies. Contractive strategies were used to resist, reject and counter alternative propositions and thus contract the dialogic space and limit the access of differing propositions. Proclaim was used to create a writer-reader relationship and to enhance authorial emphasis on the text. Disclaim was used to reject propositions concerning motherhood and postnatal depression as well as to counter propositions that would have been expected to be in the text. Disclaim was also used as a corrective strategy rather than a confrontational strategy, due to the personal expertise the women have on postnatal depression. Expansive strategies (entertain and attribute) were used to entertain propositions regarding postnatal depression and motherhood, especially expository questions were used to expand dialogic space and thus invoke discussion on the topics. Attribution was used to introduce external voices in the text to make propositions highly credible. The writers did not disalign themselves with propositions made by health care professionals, therefore expanding the dialogic space but not maximizing it. The results of this study indicate that the misconceptions and ideologies involving mental illnesses and motherhood affect the ones who fall under the categories or labels that are used in society. Women suffering from postnatal depression internalize these ideologies of how mothers should be, and when they cannot conform to these ideologies due to postnatal depression, it creates feelings of shame and guilt. This societal dialog that creates feelings of shame and guilt can be seen in the evaluative language the women used. It is important to bring awareness to the ways the social construction of motherhood and stigmatization of mental illness affect how people see themselves and how the language used in the discussion plays a part in this.